Distrust and Stigmatization of NGOS and Volunteers at the Time of the European Migrant "Crisis". Conflict and implications on social solidarity - Reggiardo, Anna (PARTECIPAZIONE E CONFLITTO, 2019)
This paper deals with the recent episodes of stigmatization of solidarity in the context of the European migrant "crisis". Securitarian measures frame as illegal not only migrants but also volunteers supporting them. Starting from the debate about "zero tolerance" policies, considered as a form of depoliticization of traditional politics, the research shows how NGOs and volunteers are becoming distrusted and conflictual, even if they long framed themselves as neutral and apolitical. An analysis of the recent emergency decrees and the decrease of trust in the Third sector, along with volunteers’ criminalization, reveals a changed picture for Third sector organizations. The Ventimiglia case study is representative of this changed context. The 11th June 2015 the French-Italian border has been closed; since then, civil society has been involved in supportive and conflictual actions about the migrants’ presence, while local politics tried to avoid political confrontation. In this situation, depoliticized politics has indirectly extended the target of its norms, stigmatizing not only migrants but also their supporters. We now deal with NGOs and volunteers conflictual and distrusted. Changes in the Third sector are helpful to consider the fragmentation and the politicization of solidarity.